Participatory Budgeting and its Diversity - Allegretti, G. (2013)
The article focuses on the participatory budget formation at the local level. The authors suggest the approach to the definition of the ‘participatory budget’, formulate the conditions for participatory budget formation, and summarize the current data on the implementation of the participatory budgeting in the international practice. The major attention is given to analyzing the models of participatory budget. The authors propose criteria for the models classification and describe the motivation of the key target groups in formulation of the participatory budget.